RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PENGGAJIAN KARYAWAN DAN GURU TETAP (STUDI PADA YAYASAN PENDIDIKAN YAMPI JAKARTA UTARA) - Widyastuti, Indria; Komalasari, Yuli; Yuliandari, Dewi (Aksara Public, 2019)
Payroll or salary management is a process of retaliating an organization's services to employees as a person who contributes to achieving organizational goals. The length of the process of making paychecks and reports can hinder the employee payroll process. The purpose of the research is to build a payroll information system that is useful to assist the activities of permanent employees and teachers of educational foundations with case studies at the Yapim Educational Foundation in the North Jakarta area. The method used in this study uses the Rational Unified Process methodology with inception, elaboration, and construction phases. The results of this study are system designs in the form of system design diagrams and payroll programs. This research is limited to the stage of construction on the software engineering methodology and testing using the blackbox testing method with the Yapim Education foundation in North Jakarta as a sample of data retrieval. This payroll information system can facilitate the management of payroll in educational foundations and this system can be used in all educational foundations by changing the profile of the organization in the system.